Occupational Health and Safety Risk Management in Toll Road Construction - Misbah Misbah; Leli Honesti; Fajar Nugroho; Meli Muchlian; Nur Hamiza Adenan; Yessy Yusnita (Universitas Pendidikan Nasional, 2026)
Construction projects carry substantial risk of work accidents. This study aims to (1) identify hazards in project activities, (2) assess and rank the associated risks, and (3) determine appropriate risk controls, using Hazard Identification, Risk Assessment, and Determining Control (HIRADC) combined with Job Safety Analysis (JSA), with Toll Road X as the case study. Of the hazards identified, none were classified as large risk; 10 were classified as medium risk and 12 as small risk. The six highest-risk findings, all medium risk, were: tripping, slipping, and falling during measurement/survey; dust exposure causing eye irritation during soil filling; slipping/falling from height during excavation; being struck by iron/steel bars; cuts from using a Bar Bender; and stepping on debris or metal during spreading. These risks may result in lost working days, permanent or partial disability, moderate environmental damage, material losses, and medical costs. Recommended risk controls include occupational health and safety (OHS) training, safety audits, use of personal protective equipment (PPE), implementation of JSA, and adoption of appropriate construction methods to reduce work accident risk.